The efect of PWHT on electrochemical behavior of AISI 316L weld metal - Kožuh, Stjepan (Array, 2008)
Summary: The subject of investigation was the corrosion behaviour of AISI 316L austenitic stainless steel weld metal as dependent on a protective passive film formed on the steel surface following exposure to w = 3.5 % NaCl. The corrosion properties were examined before PWHT and after it by means of cyclic polarization, electrochemical impedance spectroscopy, and chronoamperometric measurements. Cyclic polarization curves clearly indicated a decrease in the pitting potential following PWHT. Passivity was observed over a broad potential region. Charge transfer resistance associated with the corrosion resistance of the passive film as determined by electrochemical impedance spectroscopy indicated that high temperature PWHT acted by increasing the thickness of the passive film